Fostering Moral Education in Children: A Study Based on the Moral Values Contained in Surah An-Nisa Verse 36 - Muhammad Ali Irfan (Tadibia Islamika, 2022)
Moral education in children should be carried out as early as possible. So that when they grow up the children have noble morals. Parents, especially mothers, have the most important role in educating their children, because she is the first madrasah for their children. Children are like a pure white paper with no stains, while parents have the freedom to give any color according to what they want. The good or bad of children’s morals depend on the education provided by their parents. The objectives of this study were to find out the moral values contained in sura an-Nisa' verse 36, and to know the method of implementing moral education in children. This research used a qualitative approach with the type of field research. Data collection techniques used were interviews, observations, and documentation. The data analysis was carried out through data reduction, presentation and drawing conclusions. The results showed that the moral values contained in Sura An-Nisa' verse 36 are first, the vertical value (faith) to Allah Almighty and the prohibition of shirk. Second, the horizontal values, that is the command of doing good deeds to fellow human beings, including to both parents, relatives, orphans, poor people, close neighbors and distant neighbors, peers, travelers, and slaves; as well as the prohibition of being arrogant and self-aggrandizement, miserly and riya'. Moral education methods in children include habituation methods, exemplary methods, story methods, advice methods, and giving attention methods. This study concludes that fostering moral education in children, especially the moral values contained in surah an-nisa verse 36 is vital to be implemented in order to create good young generation.